Gender and agriculture in sub‐Saharan Africa: introduction to the special issue. (May 2015) - Kilic, Talip; Winters, Paul; Carletto, Calogero
Abstract: This special issue contributes to the literature on gender differences in sub‐Saharan African agriculture primarily by using new and innovative micro‐data. The first six articles have a strong focus on understanding the extent and drivers of gender differences in land productivity and use data from nationally representative household surveys that are implemented under the Living Standards Measurement Study‐Integrated Surveys on Agriculture (LSMS‐ISA) initiative. The LSMS‐ISA data are multi‐topic, with geo‐referenced household and plot locations, and information on production and identity of managers and owners at the plot level. The last two articles in the volume rely on in‐depth quantitative and qualitative case study data, which, in combination with the nationally representative data, allow for greater insights into the extent and correlates of gender differences in sub‐Saharan African agriculture. While there does seem to be persistent evidence of gender gaps, the studies find the sources of these gaps to vary within and across countries. This makes designing policies to address gender gaps more challenging, yet of crucial importance. What is clear is that the failure to directly and explicitly address the underlying causes of the disparities is likely to end up exacerbating the observed gender gaps.